Beyond the Bioorthogonal Inverse-Electron-Demand Diels–Alder Reactions of Tetrazines: 2-Pyrone-Functionalized Fluorogenic Probes - Cserép, Gergely B.; Németh, Krisztina; Szatmári, Ágnes; Horváth, Flóra; Imre, Tímea; Németh, Krisztina; Kele, Péter (Synthesis, 2022)
The applicability of pyrones as a bioorthogonal platform was explored in inverse-electron-demand Diels–Alder (IEDDA) reactions with a strained cyclooctyne. Studies showed that the pyrones are indeed suitable for IEDDA reactions under physiological conditions. Furthermore, the stable pyrone moiety could be utilized to construct easily accessible fluorogenic probes. Mutual orthogonality of the IEDDA reaction of 2-pyrones with SPAAC reactions of azides was also explored.
Keywords: IEDDA; bioorthogonal; 2-pyrone; fluorogenic probes; protein labeling